Development of the Interactive Storybook “Uang Pertamaku” as a Financial Literacy Learning Media for Early Childhood - Suryani, Deria; Imamah (PIAUD Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah, 2025)
Financial literacy needs to be introduced as early as possible, not only limited to the introduction of money, amounts, functions and how to use it. Financial literacy activities at Almira Preschool and Kindergarten are still not running optimally. This shows the need for financial literacy education for students at Almira Preschool and Kindergarten. This study aims to develop interactive storybooks as a medium for teaching financial literacy to early childhood. This study uses the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model approach. The targets in this study were 16 K2 students at Almira Preschool and Kindergarten, along with a teacher and the principal. Data collection techniques used observation sheets, questionnaires, and interviews. Based on the results of expert validation, a score of 86% was obtained from media experts, 88% from language experts, and 76% from subject matter experts. These results indicate that the interactive storybook “Uang Pertamaku” is suitable for use as a financial literacy learning medium for early childhood, with opportunities for improvement in terms of media appearance, language clarity, and depth of material for optimal results.